Biological activities and toxicity effects of Clinacanthus nutans (Burm.f.) lindau leaf extracts - Yu, Guk Ting (2015)
Clinacanthus nutans (C. nutans) which also known as Sabah snake grass or Pokok Belalai gajah has long been used as traditional medicines in Thailand, China and Indonesia to treat various types of diseases. Recently, C. nutans has become a popular in Malaysia as a folk medicine to treat cancer and kidney failure. Side effects arise from the used of synthetic drugs for the treatments of chronic diseases have brought about the urge to search for alternative medicine derived from natural products. Thus, the objective of this study was to determine the biological activities of the C. nutans leaf extracts. Leaves of C. nutans were extracted sequentially using hexane followed by dichloromethane, ethyl acetate, acetone and lastly distilled water. Antioxidant activity test showed that dichloromethane extract demonstrated highest free radical scavenging ability (IC50 value 106.41 ± 1.32 μg/ml). For the FRAP assay, acetone extracts exhibited highest activity with 193.00 ± 2.63 mg TE/g extract. The total phenolics contents, the acetone extract exhibited the highest value, 66.67 ± 13.85 mg GAEs/mg extract. While the dicholoromethane extract gave the highest total flavonoid contents with the value of 851.82 ± 78.06 mg QEs/mg extract. The leaf extracts have shown no inhibition on the tyrosinase activity. Anti-inflammatory activity was determined using Griess assay on nitric oxide inhibitory activity upon IFN-γ/LPS stimulated RAW 264.7 cell line showed various extracts of C. nutans have high anti-inflammatory effects with the IC50 value < 20 μg/ml except distilled water extract. Further study of in vitro toxicity test using five cultured cancer cell lines and MTT assay showed C. nutans leaf extracts exhibited selective inhibition towards the cultured cancer cell lines. Dichloromethane extract exhibited highest anti-proliferative effects on murine melanoma (B16/F10) cell line with LC50 value 48.08 μg/ml, human breast cancer (MCF-7) cell line, LC50 value 97.46 μg/ml, human colorectal carcinoma (HT- 29) cell line, LC50 value of 98.06 μg/ml, human hepatocellular carcinoma cell line (HepG2), LC50 value of 99.59 μg/ml but weakly inhibited human neuroblastoma (SYSY5Y) cell line, LC50 value156.34 μg/ml but was not toxic towards human normal Chang liver cell line with LC50 value of > 250 μg/ml. For in vivo toxicity study, the various leaf extracts tested on zebrafish embryos showed the acetone extract exhibited highest toxicity towards the embryos with LC50 value of 88.33 ± 0.58 μg/ml followed by dichloromethane extract LC50 value of 141.73 ± 3.46 μg/ml. At the higher concentration (>125 μg/ml), the embryos and larvae exhibited teratogenic effect such as coiled body, bended tail and/or tail tip, pericardial and/or yolk sac oedemas. Collectively, the study showed that the C. nutans leaf extracts possessed high antioxidant and anti-inflammatory activities as well as anti-proliferative properties against cultured cancer cell lines. This suggests the preventive and therapeutic potential of C. nutans leaf to be used as alternative medicines for various types of diseases including cancer in the future.